Prevalence of toxoplasma, cytomegalovirus and rubella in pregnant women in Erzurum, Turkey (Annals of Medical Research, 2021)
Aim: In this study, the seroprevalence of IgM- and IgG- type antibodies against Toxoplasma, Cytomegalovirus (CMV) and Rubellavirus was investigated in pregnant women with routine controls performed by family physicians in the city center of Erzurum in atwo-year period. It was aimed to compare the obtained data with other studies conducted in our country and in the world.Materials and Methods: The specific results of IgM and IgG serology of Toxoplasma, CMV and rubella of 6798 pregnant womenperformed by family physicians in the city center of Erzurum between 01.01.2018 and 31.12.2019 were investigated and evaluatedaccording to different age groups in this retrospective cross-sectional study. The serum samples were studied using the Architecti2000 systems with the Chemiluminescent Microparticle Immunoassay (CMIA) method in Erzurum Public Health MicrobiologyLaboratory.Results: The data of 6798 people between the ages of 15-50 were reached in our study. Toxoplasma, Rubella and CMV- (n = 6586)specific IgM antibody seropositivity rates were found as 0.5%, 0.3% and 0.6%, respectively, while Toxoplasma-, Rubella- and CMV-specific IgG antibody seropositivity rates were found as 20.9%, 88.3% and 99.2%, respectively. Toxoplasma IgG seropositivity rateswere determined to increase in parallel with increasing age. Rubella IgG seropositivity rates were decreasing in the 15-24, 25-34 and35-49 age groups, respectively. The lowest Toxoplasma IgM and CMV IgM seropositivity rates were found in the 35-49 age groups.Conclusions: The two-year seroprevalence of Toxoplasma, CMV and Rubella was determined in pregnant women in our region withthis study. Although these seroprevalence rates in Erzurum are generally compatible with other studies conducted in our country,Toxoplasma IgM and rubella IgG seropositivity rates were found to be lower compared to the overall incidence of our country.